MODELING ARIMA AND LSTM TIME SERIES MODELS IN PYTHON - Дорошенко, Ірина; Тарасов, Максим (SWorldJournal, 2025)
This article examines the theoretical foundations and practical aspects of applying ARIMA models, RNN architecture, and the working principles of LSTM, as well as their use for time series forecasting in Python using the Statsmodels and Keras libraries.